STRATEGI PENGEMBANGAN USAHATANI PADA KAMPUNG REFORMA AGRARIA DI KABUPATEN MUARA ENIM - Yahya, M Zamzami; Maryadi, Maryadi; Adriani, Dessy (AGROTEKSOS, 2024)
Agrarian reform fundamentally provides programs which can solve the problem of poverty in rural communities, improving welfare with national food independence, increase land productivity, provide recognition of land rights owned both privately, state, and publicly owned land that its use to meet the interests of the community. The purpose of this study was to develop a strategy for the development of sustainability from the Agrarian Reform Village. This research was conducted in Bitis Village Gelumbang District, Muara Enim Regency in December 2024. The research methods used are case study methods and simple random sample sampling methods. The data used are primary and secondary data. The results of this study is oyster mushroom farming and oyster mushroom chip snack businesses are in quadrant II (W-O) which needs to implement a business transformation strategy by overcoming the weaknesses in their business by taking advantage of existing opportunities.